PENERAPAN MEDIA FLIPBOOK MODEL TARL UNTUK MENINGKATKAN LITERASI MEMBACA SISWA KELAS I SD INPRES KAMPUNG MEJANG KECAMATAN BONTONOMPO KABUPATEN GOWA: PENELITIAN TINDAKAN KELAS - Arfiah, Mar’atul; Bahri, Aliem; Asnidar, Anin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mar’atul Arfiah, 2025. The Application of Flipbook Media with the TaRL Model to Improve Reading Literacy of Grade I Students at SD Inpres Kampung Mejang, Bontonompo District, Gowa Regency. Undergraduate Thesis, Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I: Aliem Bahri, Supervisor II: Anin Asnidar. The problem in this research is the low reading achievement of Grade I students at SD Inpres Kampung Mejang, Bontonompo District, Gowa Regency. This study aims to determine whether the use of Flipbook media with the TaRL model can improve the reading literacy of Grade I students at SD Inpres Kampung Mejang, Bontonompo District, Gowa Regency. This research is a Classroom Action Research (CAR), conducted in two cycles, with each cycle consisting of three meetings. Each cycle went through four stages: planning, implementation, observation, and reflection. The subjects of this study were 33 Grade I students at SD Inpres Kampung Mejang. The data collection techniques used were observation, tests, and documentation. The data analysis technique applied was descriptive statistical analysis. Based on the analysis of test results in Cycle I, out of 33 students, only 11 students (33.3%) achieved mastery, while 22 students (66.6%) were still in the non-mastery category. This shows that the majority of students had not yet reached the Minimum Mastery Criteria (KKM). In Cycle II, out of 33 students, 31 students (93.9%) achieved mastery, while only 2 students (6%) were still in the non-mastery category. These results indicate that most students successfully met the minimum mastery standard, proving that learning in Cycle II was effective and significantly improved students’ learning outcomes.The conclusion of this study is that the application of Flipbook media with the TaRL model can improve the reading literacy of Grade I students at SD Inpres Kampung Mejang, Bontonompo District, Gowa Regency.